2020
DOI: 10.1155/2020/8894727
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Typing of Klebsiella pneumoniae Clinical Isolates by Enterobacterial Repetitive Intergenic Consensus Polymerase Chain Reaction

Abstract: Aim. Klebsiella pneumoniae is one of the most important causes of nosocomial infections, including pneumonia, sepsis, and urinary tract infection. Enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR) technique is a quick, reliable, and cost-effective method for molecular typing of Enterobacteriaceae family members. This study aimed to detect genetic relatedness among K. pneumoniae isolates from hospitals in Hamadan city, using ERIC-PCR technique. Materials and Methods. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 15 publications
(19 reference statements)
1
19
0
Order By: Relevance
“…These may originate from a common ancestral strain, demonstrating cross-transmission between chickens and humans. A recent study in Iran showed immense genetic diversity among K. pneumoniae isolates from hospitalized patients [ 69 ]. Moreover, another Indian study demonstrated heterogeneous K. pneumoniae human isolates while using ERIC-PCR, suggesting the involvement of multiple subtypes in infection [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…These may originate from a common ancestral strain, demonstrating cross-transmission between chickens and humans. A recent study in Iran showed immense genetic diversity among K. pneumoniae isolates from hospitalized patients [ 69 ]. Moreover, another Indian study demonstrated heterogeneous K. pneumoniae human isolates while using ERIC-PCR, suggesting the involvement of multiple subtypes in infection [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high diversity of K. pneumoniae isolates in the present study is an important finding because more than 70% of these isolates are MDR and can use mechanisms such as horizontal gene transfer to transfer this resistance to the bacteria which induce healthcare-associated infections. Different clones may have different antimicrobial resistance patterns and thereby can cause more difficulties in the treatment of their associated infections [22]. Given the significant role of antimicrobial resistance in the management of VAP, the high prevalence of resistant strains can complicate the conditions of patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) based on ERIC (ERIC-PCR) has successfully been used for the genotyping, strain diversity assessment, population analysis, and epidemiological assessments of different microbial pathogens and determining their taxonomy and phylogenetic relatedness [21]. Compared with other typing methods such as ribotyping, Pulse Field Gel Electrophoresis, and Multilocus Sequence Typing, ERIC-PCR is considered as a faster, more reliable, and more cost-effective technique for the molecular typing and the genetic diversity assessment of the Enterobacteriaceae family [22].…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial resistance is an important concern in the public health systems that due to the rise in the resistant strains of bacteria (Nouri et al, 2020). And the enterobacterial repetitive intergenic consensus sequences polymerase chain reaction (ERIC-PCR) is a simple, fast, and affordable PCR-based methods for molecular typing analysis of different isolated bacteria, which were less dependent on effective and variable factors on bacterial growth (Sedighi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%